PENERAPAN PBL DALAM DEBAT BAHASA INDONESIA DI KELAS X - Angga, Angga Jean Gloria Laratmase (Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study aims to describe the implementation of the Project Based Learning (PJBL) model in Indonesian language debate learning and its impact on the logical thinking skills of Grade X students at SMTKN Diaspora Kabupaten Sorong. The background of this research is the students’ low ability to express arguments in a structured and logical manner. This research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and tests. The results show that the implementation of PJBL increases student activeness in discussions, courage to express opinions, and the ability to construct logical arguments. A total of 62% of students achieved scores above the minimum mastery criteria. These findings indicate that the PJBL model is effective in developing students' logical thinking skills through debate activities. This model is considered suitable for use in Indonesian language learning as an effort to encourage active, creative, and collaborative learning.